Variable pH habitats could help prepare stone crabs for coastal acidification - Philip M. Gravinese; Hannah E. Craft; Alex Douwes; Gretchen S. Faraci; Morgan L. Jarrett; Shelby A. Perry; Chloe E. Potts; Emma C. Rosser; Abigail L. Smith; Alexis R. Trevillian; Christopher Moore; Kimberly K. Yates (Marine Biology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Examining the relationship between air masses and Aedes aegypti presence in US counties using explainable artificial intelligence - Chibuike Chiedozie Ibebuchi; Cameron C. Lee; Itohan-Osa Abu; Omon A. Obarein; Alindomar Silva; Seth Rainey; Oluwaferanmi O. Akinyemi; Kaylie Craft (Theoretical and Applied Climatology, 2026)
Aedes aegypti mosquitoes are primary vectors for viral diseases including Zika, Dengue, Chikungunya, and Yellow Fever. Understanding the climatic factors influencing their proliferation is crucial for targeted vector control strategies. This study investigates the relationship between air mass (AM) categories and the annual and seasonal presence of Aedes aegypti in Manatee County, Florida, using data spanning from 1979 to 2024 sourced from the Global Biodiversity Information Facility. We employed Spearman correlations and explainable artificial intelligence (XAI), specifically a gradient boosting classifier integrated with Shapley additive explanations (SHAP), to investigate these relationships. Our findings highlight a pronounced seasonal cycle, with mosquito presence peaking in summer months (July-August) and minimizing during winter (December-March). At the annual scale, significant correlations were identified between mosquito presence and specific air mass conditions: humid warm (HW) AMs positively correlated (ρ = 0.39), suggesting enhanced presence under humid and warm environments, whereas cold (C) AMs negatively correlated (ρ = −0.34), indicative of reduced presence under colder conditions. Seasonal analyses using SHAP and Spearman correlations revealed that during summer, dry cold (DC) and dry (D) AM categories significantly decrease mosquito populations, collectively accounting for 22% of the model’s explanatory power. Conversely, warm AM emerged as a critical positive predictor in summer, contributing to 20% of the model’s predictive capability. Further, DC air masses in summer negatively impacted autumn mosquito presence (9.2% SHAP contribution) possibly by suppressing conditions favorable for proliferation in the peak breeding summer months. Comparative analysis with other counties exhibiting distinct climatic profiles provides broader applicability. These insights guide mosquito-borne disease risk management, guiding strategic interventions tailored to regional climatic conditions.

Intraspecific trait shift reflects earthworm response to land-use intensification in peat grasslands - Lianne C. Woudstra; Jacintha Ellers; Mariet M. Hefting; Taylor B. Craft; Matty P. Berg (Applied Soil Ecology, 2026)

Age, glucose tolerance, and cognitive performance in female vervet monkeys - Brett M. Frye; Trinity G. Davis; Haiying Chen; Thomas C. Register; Suzanne Craft; Mark G. Baxter; Carol A. Shively (GeroScience, 2025)

Evaluation of SARS-CoV-2 antibody detection methods for wild Cervidae - Joshua Hewitt; Grete Wilson-Henjum; Jeffrey C. Chandler; Aaron T. Phillips; Diego G. Diel; W. David Walter; Alec Baker; Jennifer Høy-Petersen; Guillaume Bastille-Rousseau; Tadao Kishimoto; George Wittemyer; Jeremy Alder; et al. (Preventive Veterinary Medicine, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Mesopredator release moderates trophic control of plant biomass in a Georgia salt marsh - Joseph P. Morton; Marc J. S. Hensel; David S. DeLaMater; Christine Angelini; Rebecca L. Atkins; Kimberly D. Prince; Sydney L. Williams; Anjali D. Boyd; Jennifer Parsons; Emlyn J. Resetarits; Carter S. Smith; Stephanie Valdez; et al. (Ecology, 2024)
Predators regulate communities through top‐down control in many ecosystems. Because most studies of top‐down control last less than a year and focus on only a subset of the community, they may miss predator effects that manifest at longer timescales or across whole food webs. In southeastern US salt marshes, short‐term and small‐scale experiments indicate that nektonic predators (e.g., blue crab, fish, terrapins) facilitate the foundational grass, Spartina alterniflora , by consuming herbivorous snails and crabs. To test both how nekton affect marsh processes when the entire animal community is present, and how prior results scale over time, we conducted a 3‐year nekton exclusion experiment in a Georgia salt marsh using replicated 19.6 m 2 plots. Our nekton exclusions increased densities of plant‐grazing snails and juvenile deposit‐feeding fiddler crab and, in Year 2, reduced predation on tethered juvenile snails, indicating that nektonic predators control these key macroinvertebrates. However, in Year 3, densities of mesopredatory benthic mud crabs increased threefold in nekton exclusions, erasing the tethered snails' predation refuge. Nekton exclusion had no effect on Spartina biomass, likely because the observed mesopredator release suppressed grazing snail densities and elevated densities of fiddler crabs, whose burrowing alleviates soil stresses. Structural equation modeling supported the hypotheses that nektonic predators and mesopredators control invertebrate communities, with nektonic predators having stronger total effects on Spartina than mud crabs by controlling densities of species that both suppress (grazers) and facilitate (fiddler crabs) plant growth. These findings highlight that salt marshes can be resilient to multiyear reductions in nektonic predators if mesopredators are present and that multiple pathways of trophic control manifest in different ways over time to mediate community dynamics. These results highlight that larger scale and longer‐term experiments can illuminate community dynamics not previously understood, even in well‐studied ecosystems such as salt marshes.

Resistance and resilience: Tidal freshwater marsh response and recovery to acute and chronic saltwater intrusion - Madeleine F. Thompson; Steve C. Pennings; Joseph P. Schubauer-Berigan; Ellen R. Herbert; Galen Costomiris; Christopher B. Craft (Estuarine, Coastal and Shelf Science, 2024)

Modeling the risk of aquatic species invasion spread through boater movements and river connections - Amy C. Kinsley; Szu‐Yu Zoe Kao; Eva A. Enns; Luis E. Escobar; Huijie Qiao; Nicholas Snellgrove; Ulirich Muellner; Petra Muellner; Ranjan Muthukrishnan; Meggan E. Craft; Daniel J. Larkin; Nicholas B. D. Phelps (Conservation Biology, 2024)
Aquatic invasive species (AIS) are one of the greatest threats to the functioning of aquatic ecosystems worldwide. Once an invasive species has been introduced to a new region, many governments develop management strategies to reduce further spread. Nevertheless, managing AIS in a new region is challenging because of the vast areas that need protection and limited resources. Spatial heterogeneity in invasion risk is driven by environmental suitability and propagule pressure, which can be used to prioritize locations for surveillance and intervention activities. To better understand invasion risk across aquatic landscapes, we developed a simulation model to estimate the likelihood of a waterbody becoming invaded with an AIS. The model included waterbodies connected via a multilayer network that included boater movements and hydrological connections. In a case study of Minnesota, we used zebra mussels ( Dreissena polymorpha ) and starry stonewort ( Nitellopsis obtusa ) as model species. We simulated the impacts of management scenarios developed by stakeholders and created a decision‐support tool available through an online application provided as part of the AIS Explorer dashboard. Our baseline model revealed that 89% of new zebra mussel invasions and 84% of new starry stonewort invasions occurred through boater movements, establishing it as a primary pathway of spread and offering insights beyond risk estimates generated by traditional environmental suitability models alone. Our results highlight the critical role of interventions applied to boater movements to reduce AIS dispersal.

Metal accumulation in salt marsh soils along the East Coast of the United States - Kristen E. Jezycki; Elise Rodriguez; Christopher B. Craft; Scott C. Neubauer; James T. Morris; Steven T. Goldsmith; Peleg Kremer; Nathaniel B. Weston (Science of The Total Environment, 2024)

Microbiome diversity and zoonotic bacterial pathogen prevalence in Peromyscus mice from agricultural landscapes and synanthropic habitat - Janine Mistrick; Evan J. Kipp; Sarah I. Weinberg; Collin C. Adams; Peter A. Larsen; Meggan E. Craft (Molecular Ecology, 2024)
Rodents are key reservoirs of zoonotic pathogens and play an important role in disease transmission to humans. Importantly, anthropogenic land‐use change has been found to increase the abundance of rodents that thrive in human‐built environments (synanthropic rodents), particularly rodent reservoirs of zoonotic disease. Anthropogenic environments also affect the microbiome of synanthropic wildlife, influencing wildlife health and potentially introducing novel pathogens. Our objective was to examine the effect of agricultural development and synanthropic habitat on microbiome diversity and the prevalence of zoonotic bacterial pathogens in wild Peromyscus mice to better understand the role of these rodents in pathogen maintenance and transmission. We conducted 16S amplicon sequencing on faecal samples using long‐read nanopore sequencing technology to characterize the rodent microbiome. We compared microbiome diversity and composition between forest and synanthropic habitats in agricultural and undeveloped landscapes and screened for putative pathogenic bacteria. Microbiome richness, diversity, and evenness were higher in the agricultural landscape and synanthropic habitat compared to undeveloped‐forest habitat. Microbiome composition also differed significantly between agricultural and undeveloped landscapes and forest and synanthropic habitats. We detected overall low diversity and abundance of putative pathogenic bacteria, though putative pathogens were more likely to be found in mice from the agricultural landscape. Our findings show that landscape‐ and habitat‐level anthropogenic factors affect Peromyscus microbiomes and suggest that landscape‐level agricultural development may be important to predict zoonotic pathogen prevalence. Ultimately, understanding how anthropogenic land‐use change and synanthropy affect rodent microbiomes and pathogen prevalence is important to managing transmission of rodent‐borne zoonotic diseases to humans.

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Statewide prioritization of vernal pools for pond-breeding amphibians in New Jersey - Hannah E. Craft; Geoffrey Fouad; Sean C. Sterrett (Journal of Environmental Management, 2023)

Executive function mediates age-related variation in social integration in female vervet monkeys (Chlorocebus sabaeus) - Jacob D. Negrey; Brett M. Frye; Suzanne Craft; Thomas C. Register; Mark G. Baxter; Matthew J. Jorgensen; Carol A. Shively (GeroScience, 2023)

Defining an epidemiological landscape that connects movement ecology to pathogen transmission and pace‐of‐life - Kezia Manlove; Mark Wilber; Lauren White; Guillaume Bastille‐Rousseau; Anni Yang; Marie L. J. Gilbertson; Meggan E. Craft; Paul C. Cross; George Wittemyer; Kim M. Pepin (Ecology Letters, 2022)
Pathogen transmission depends on host density, mobility and contact. These components emerge from host and pathogen movements that themselves arise through interactions with the surrounding environment. The environment, the emergent host and pathogen movements, and the subsequent patterns of density, mobility and contact form an ‘epidemiological landscape’ connecting the environment to specific locations where transmissions occur. Conventionally, the epidemiological landscape has been described in terms of the geographical coordinates where hosts or pathogens are located. We advocate for an alternative approach that relates those locations to attributes of the local environment. Environmental descriptions can strengthen epidemiological forecasts by allowing for predictions even when local geographical data are not available. Environmental predictions are more accessible than ever thanks to new tools from movement ecology, and we introduce a ‘movement‐pathogen pace of life’ heuristic to help identify aspects of movement that have the most influence on spatial epidemiology. By linking pathogen transmission directly to the environment, the epidemiological landscape offers an efficient path for using environmental information to inform models describing when and where transmission will occur.

Correction to: Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

Characterization of mule deerpox virus in Florida white-tailed deer fawns expands the known host and geographic range of this emerging pathogen - Katherine A. Sayler; Kuttichantran Subramaniam; Jessica M. Jacob; Julia C. Loeb; William F. Craft; Lisa L. Farina; Nicole I. Stacy; Nissin Moussatche; Laurie Cook; John A. Lednicky; Samantha M. Wisely; Thomas B. Waltzek (Archives of Virology, 2019)

Spatial and Temporal Dynamics of Invasive Freshwater Shrimp (Mysis diluviana): Long-Term Effects on Ecosystem Properties in a Large Oligotrophic Lake - Shawn P. Devlin; Samantha K. Tappenbeck; James A. Craft; Tyler H. Tappenbeck; Dale W. Chess; Diane C. Whited; Bonnie K. Ellis; Jack A. Stanford (Ecosystems, 2017)

Carbon Sequestration in Tidal Salt Marshes of the Northeast United States - Katherine Drake; Holly Halifax; Susan C. Adamowicz; Christopher Craft (Environmental Management, 2015)

Height at diagnosis and birth-weight as risk factors for osteosarcoma - Lisa Mirabello; Ruth Pfeiffer; Gwen Murphy; Najat C. Daw; Ana Patiño-Garcia; Rebecca J. Troisi; Robert N. Hoover; Chester Douglass; Joachim Schüz; Alan W. Craft; Sharon A. Savage (Cancer Causes & Control, 2011)

Endoglin suppresses human prostate cancer metastasis - Minalini Lakshman; Xiaoke Huang; Vijayalakshmi Ananthanarayanan; Borko Jovanovic; Yueqin Liu; Clarissa S. Craft; Diana Romero; Calvin P. H. Vary; Raymond C. Bergan (Clinical & Experimental Metastasis, 2011)

Ecosystem Functions of Tidal Fresh, Brackish, and Salt Marshes on the Georgia Coast - Kazimierz Więski; Hongyu Guo; Christopher B. Craft; Steven C. Pennings (Estuaries and Coasts, 2010)

Oligogenic combinations associated with breast cancer risk in women under 53years of age - Christopher E. Aston; David A. Ralph; Dominique P. Lalo; Sharmila Manjeshwar; Bobby A. Gramling; Daniele C. DeFreese; Amy D. West; Dannielle E. Branam; Linda F. Thompson; Melissa A. Craft; Debra S. Mitchell; Craig D. Shimasaki; et al. (Human Genetics, 2005)

Spectroscopic and computational characterization of the nickel-containing F430 cofactor of methyl-coenzyme M reductase - Jennifer L. Craft; Yih-Chern Horng; Stephen W. Ragsdale; Thomas C. Brunold (JBIC Journal of Biological Inorganic Chemistry, 2004)

Co-development of wetland soils and benthic invertebrate communities following salt marsh creation - C. Craft (Wetlands Ecology and Management, 2000)

Co-development of wetland soils and benthic invertebrate communities following salt marsh creation - C. Craft (Wetlands Ecology and Management, 2000)

The 18th congress of the israeli phytopathological society - Y. Elad; D. Shtienberg; H. Vintal; Y. Cohen; Sonia Farkash; Zipora Reshit; A. Baider; Edna Levy; I. S. Ben-Ze’ev; Y. Nitzani; Frieda Kleitman; Talma Katan; et al. (Phytoparasitica, 1997)

Respiration of potato tissue as influenced by previous storage temperature of the tubers - C. C. Craft (American Journal of Potato Research, 1967)

Localization and activity of phenolase in the potato tuber - C. C. Craft (American Journal of Potato Research, 1966)

Respiration of potatoes as influenced by previous storage temperature - C. C. Craft (American Journal of Potato Research, 1963)

Some effects of isopropyl N-(3-chlorophenyl) carbamate on respiration, water uptake and ion leakage of potato tissue - C. C. Craft; William V. Audia (American Journal of Potato Research, 1959)

Study of the phenolic compounds in potato tubers during storage - C. C. Craft; H. W. Siegelman; W. L. Butler (American Journal of Potato Research, 1958)

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)

Effects of some metabolic inhibitors on sugar accumulation in potato discs during partial desiccation - C. C. Craft (American Journal of Potato Research, 1956)

Further tests with 3-chloro-isopropyl-N-phenyl carbamate as a sprout inhibitor for potato tubers - P. H. Heinze; Paul C. Marth; C. C. Craft (American Journal of Potato Research, 1955)

Variations in specific gravity of potatoes - P. H. Heinze; C. C. Craft; Beatrice M. Mountjoy; Mary E. Kirkpatrick (American Journal of Potato Research, 1952)

Association of specific gravity with weight of individual tubers in late crop potatoes - C. C. Craft; P. H. Heinze (American Journal of Potato Research, 1951)